Wavelet based technique for multi-crack detection of a beam-like structure using the vibration data measured directly from a moving vehicle - Viet Khoa, Nguyen; Thanh Hai, Tran (Vietnam Journal of Mechanics, 2010)
In this paper an idea for crack detection of a multi-cracked beam-like structure by analyzing the vibration measured directly from the vehicle is presented. The crack model is adopted from fracture mechanics. The dynamic response of the bridge-vehicle system is measured directly from the moving vehicle. When the vehicle moves along the structure, the dynamic response of the vehicle is distorted by the cracks at their locations. These distortions are generally small and difficult to be detected visually. In order to detect the cracks, Wavelet Transform - an effective method of detecting such small distortions was adopted. The existence of the cracks can be revealed by large values (peaks) in the wavelet transform. Locations of the cracks can be determined by positions of the peaks and the vehicle speed. Numerical results show that the method can detect cracks as small as 10 % of the beam height with noise level up to 5%. The proposed method is applicable for low velocity-movements while high velocity-movements are not recommended.